2018
DOI: 10.1111/tri.13137
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate in stable older kidney transplant recipients-are present algorithms valid? A national cross-sectional cohort study

Abstract: Several equations have been developed for estimated glomerular filtration rate (eGFR) in patients with chronic kidney disease (CKD), but none were developed based on data from elderly kidney transplant recipients (KTR). The primary aim of this study was to evaluate different creatinine-based equations in stable elderly KTR. A national cross-sectional study was performed using data from 263 consecutive kidney transplant recipients 60 years or older who performed a routine GFR measurement one year after engraftm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our population of KTR patients is comparable to those of other studies in terms of GFR level as the majority of reported KTR population have an eGFR<60 mL/min/1.73 m 2 after one year. [3,5,9,10,12,14,[25][26][27]. In the present study, the mean mGFR one year after graft was close to the other KTR populations i.e.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…Our population of KTR patients is comparable to those of other studies in terms of GFR level as the majority of reported KTR population have an eGFR<60 mL/min/1.73 m 2 after one year. [3,5,9,10,12,14,[25][26][27]. In the present study, the mean mGFR one year after graft was close to the other KTR populations i.e.…”
Section: Plos Onesupporting
confidence: 82%
“…[17] In recent publication, the LMR equation showed the best performance in 263 KTR aged >60 years with a mGFR <60 mL/min/1.73m 2 . [26] In the present study, the LMR equation predicted GFR more precisely and accurately than MDRD, CKD-EPI, and FAS equations in the total KTR population. Several hypothesis could be given to explain this result: first, the possible difference of GFR determination method for the development of MDRD et LMR equations (urinary iothalamate clearance and plasma iohexol clearance, respectively) and secondly the fact that LMR equation was developed with the goal of improving estimations at low mGFR levels.…”
Section: Plos Onementioning
confidence: 45%
“…The MDRD equation overestimates GFR in the elderly [ 28 , 29 , 30 ]. Heldal et al found that BIS, CG, FAS, and LMR were more accurate than CKD-EPI in stable elderly kidney transplant patients [ 38 ], while results from several other studies have proven that CG underestimates GFR in the elderly [ 31 , 32 ]. The BIS equation was developed specifically in elderly patients and seems to be the most promising alternative to CKD-EPI.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics present a diagnostic challenge for the emergency physician when assessing for pulmonary embolus in kidney transplant recipients. As a result this population is at risk for iodine contrast-induced nephropathy at higher rates than patients with bilateral native kidney function with similar estimated glomerular filtration rate (eGFR) 7 , 8 ; however, it is unclear whether this broadly applies to patients with chronic kidney disease (CKD) and a decreased renal reserve in the setting of a solitary kidney transplant since this group is either excluded or under-represented in multivariate analyses. 9 We report the use of ferumoxytol-enhanced magnetic resonance angiography (FeMRA) as an alternative diagnostic tool to assess for pulmonary embolus in patients at risk of iodine contrast-induced nephropathy.…”
Section: Introductionmentioning
confidence: 99%